Synchronization between non-autonomous hyperchaotc systems with uncertainties using active control method - Yadav, Vijay K.; Mishra, Prashant K.; Srivastava, Mayank; and et al (Elsevier B.V., 2016)
In this article authors have studied the synchronization between non-autonomous hyperchaotic systems viz., Liu and 4D hyperchaotic non-autonomous systems with parametric uncertainties using active control method. The numerical simulation and graphical results shows that the considered method is effective to synchronize non-autonomous hyperchaotic systems with parametric uncertain terms.
Keywords: Active control method; Non-autonomous hyperchaotic systems; Synchronization; Uncertain parameters